Characterization of Acetolactate Synthase (ALS)-Inhibitor Resistance in Pennsylvania smartweed (Persicaria pensylvanica). Issue 6 (21st September 2018) - Varanasi, Vijay K.; Norsworthy, Jason K.; Brabham, Chad; Scott, Robert C.
Abstract: Pennsylvania smartweed [ Persicaria pensylvanica (L.) M. Gómez] is a common weed of rice ( Oryza sativa L.) in the midsouthern United States and has recently become a concern for farmers because of reduced tillage systems. Acetolactate synthase (ALS) inhibitors have been extensively used for controlling smartweeds in imidazolinone-resistant and conventional rice. In the present study, we confirmed resistance to commonly used ALS inhibitors in rice and characterized the underlying resistance mechanism in a P. pensylvanica biotype from southeast Missouri. A dose–response experiment was conducted in the greenhouse using bensulfuron-methyl, imazethapyr, and bispyribac-sodium to determine the resistance index (resistance/susceptibility [R/S]) based on GR50 estimates. The target-site ALS gene was amplified from R and S plants, and sequences were analyzed for mutations known to confer ALS-inhibitor resistance. The P. pensylvanica biotype in question was found to be resistant to bensulfuron-methyl (R/S=2, 330), imazethapyr (R/S=12), and bispyribac-sodium (R/S=6). Sequencing of the ALS gene from R plants revealed two previously known mutations (Pro-197-Ser, Ala-122-Ser) conferring resistance to sulfonylureas and imidazolinones. This is the first report of ALS-inhibitor resistance in P. pensylvanica .